2013
DOI: 10.1038/hr.2013.51
|View full text |Cite
|
Sign up to set email alerts
|

Renin–angiotensin–aldosterone system has a pivotal role in cognitive impairment

Abstract: Because dementia is associated with both deterioration in the quality of life and poor prognosis, the prevention of cognitive impairment (CI) is a critical problem in public health promotion. Hypertension is a risk factor for the aggravation of CI, and the renin-angiotensin-aldosterone system (RAAS) is a key player in the increased incidence and development of hypertension. Therefore, the RAAS is considered to be a promoting factor for CI development. Conversely, recent studies have shown that lowering blood p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 92 publications
1
20
0
Order By: Relevance
“…These results were found to be in agreement with earlier studies that show significantly higher blood pressure, right kidney weight and heart weight in DOCA salt-induced hypertensive rats as compared to the sham operated rats (Hacioglu et al, 2003). Hypertension is one of the most critical risk factors for cognitive impairment and the renin angiotensin aldosterone system (RAAS) is a key player in hypertension, both in a blood pressure-dependent and-independent manner (Yagi et al, 2011;Yagi et al, 2013). The functional mechanisms of hypertension increasing the risk of cognitive impairment remain ambiguous.…”
Section: Discussionsupporting
confidence: 94%
“…These results were found to be in agreement with earlier studies that show significantly higher blood pressure, right kidney weight and heart weight in DOCA salt-induced hypertensive rats as compared to the sham operated rats (Hacioglu et al, 2003). Hypertension is one of the most critical risk factors for cognitive impairment and the renin angiotensin aldosterone system (RAAS) is a key player in hypertension, both in a blood pressure-dependent and-independent manner (Yagi et al, 2011;Yagi et al, 2013). The functional mechanisms of hypertension increasing the risk of cognitive impairment remain ambiguous.…”
Section: Discussionsupporting
confidence: 94%
“…It has been reported that vascular inflammation is associated with cognitive function [ 16 ]. EPA is known to have the ability to attenuate tumor necrosis factor-α-induced upregulation of vascular cell adhesion molecule-1, intercellular adhesion molecule-1, and monocyte chemoattractant protein-1 [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of angiotensin 1 receptor is associated with inflammation, blood–brain barrier damage and a decrease in blood brain flow. In this context, an inhibition of the RAAS in the hippocampus (which plays a significant part in cognition) using blood–brain barrier-penetrating RAAS inhibitors may have favorable effects in preventing cognitive decline [63]. Therapy with ARBs and ACEIs, particularly using brain-penetrating drugs such as captopril, perindopril and telmisartan appears to improve blood–brain barrier function, increase cerebral blood flow and reduce inflammation.…”
Section: Introductionmentioning
confidence: 99%